Leishmaniosis in Rodents Caused by Leishmania infantum: A Review of Studies in the Mediterranean Area - Alcover, M. Magdalena; Riera, M. Cristina; Fisa, Roser (Frontiers in Veterinary Science, 2021)
Leishmaniosis infection begins when a phlebotomine sand fly vector inoculates pathogenic protozoan parasites of the genus Leishmania into a mammalian host. In the case of Leishmania infantum, the domestic dog is considered to be the main parasite reservoir, and canine leishmaniosis (CanL) has a high mortality rate in untreated dogs. Hundreds of cases of human leishmaniosis (HL) are reported in the world each year, the incidence in Europe being relatively low. Leishmaniosis control is primarily focused on the dog, combining methods that prevent sand fly bites and boost host resistance to infection. However, these measures are only partially effective and new solutions need to be found. One of the main factors limiting CanL and HL control is the existence of a sylvatic Leishmania transmission cycle that interacts with the domestic cycle maintained by dogs. It is suspected that the main reservoir of infection in wildlife are rodents, whose expansion and rapid population growth worldwide is increasing the risk of human and zoonotic pathogen transfer. The aim of this review is therefore to analyze reports in the literature that may shed light on the potential role of rodents in the leishmaniosis transmission cycle in the Mediterranean area. Following the general methodology recommended for reviews, six databases (Google Scholar, Ovid, PubMed, Science Direct, Scopus and Web of Science) were explored for the period January 1995 to December 2020. The results extracted from 39 publications that met the established inclusion criteria were analyzed. It was found that 23 species of rodents have been studied in nine countries of the Mediterranean basin. Of the 3,643 specimens studied, 302 tested positive for L. infantum infection by serology, microscopy and / or molecular techniques.